2012
DOI: 10.1002/cite.201200135
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Mechanical Stress Caused to CHO Suspension Cells by Standard and Single‐Use Pumps

Abstract: Mechanical stress caused to transfected Chinese hamster ovary (CHO) suspension cells by reusable and single‐use magnetically levitated, bearingless centrifugal pumps was investigated. Cell death rates were determined for different pump speeds and compared with data from a peristaltic and a 4‐piston diaphragm pump. Furthermore, the fluid distribution inside the PuraLev® 200 pump was modeled using computational fluid dynamics. The results reveal considerably lower mechanical stress to CHO cells caused by the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
9
25
0
Order By: Relevance
“…The impact of using a manifold and peristaltic pumps for cell culture broth recirculation is observed on Figure b, where an initial viability decay is observed on the Day 3 corresponding to the media exchange start. This observation is in‐line with the Blaschczok et al () study on the impact of peristaltic pumps on cell culture viability. The increased mechanical stress by the peristaltic pump leads to the release of intracellular components and an increase of cell debris creating a more challenging filtration scenario.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The impact of using a manifold and peristaltic pumps for cell culture broth recirculation is observed on Figure b, where an initial viability decay is observed on the Day 3 corresponding to the media exchange start. This observation is in‐line with the Blaschczok et al () study on the impact of peristaltic pumps on cell culture viability. The increased mechanical stress by the peristaltic pump leads to the release of intracellular components and an increase of cell debris creating a more challenging filtration scenario.…”
Section: Resultssupporting
confidence: 90%
“…This observation is in-line with the Blaschczok et al (2013) study on the impact of peristaltic pumps on cell culture viability. The increased mechanical stress by the peristaltic pump leads to the release of intracellular components and an increase of cell debris creating a more challenging filtration scenario.…”
Section: Tff Membrane Screeningsupporting
confidence: 89%
“…However, the use of peristaltic pumps can lead to significant hydrodynamic damage, affecting cell growth and cell viability, which is furthermore strongly dependent on the specific cell line and clone [12,43]. Therefore, other circulation systems as syringe pumps or centrifugal pumps might be more suitable for the application in scale-down models [12,44]. However, batch fermentations including a recirculation loop and peristaltic pumps revealed no effects of the circulation system on the applied cell line in this study (data not shown) and thus the circulation system was not considered to be the root cause for the decreased cell growth in the two-compartment system.…”
Section: Evaluation Of Growth Characteristics Of the Twocompartment Smentioning
confidence: 99%
“…During the pumping process, mechanical stress can result in irreversible cell damage, which might impair the quantity and quality of the product [1][2][3][4] . The level of mechanical stress depends on the pump type and pump settings, as demonstrated in previous studies [5][6] . Commonly, peristaltic, syringe and diaphragm pumps are used for single-use (SU) technology based applications.…”
Section: Introductionmentioning
confidence: 94%
“…The motor is magnetically driven in order to avoid narrow gaps between the impeller and the pump housing (Figure 1). A previous study investigated the MagLev centrifugal pumps and showed lower mechanical stress in Chinese Hamster Ovary (CHO) cells compared with peristaltic and 4-piston diaphragm pumps 5 . In addition, hemolysis analyses revealed no significant blood trauma and thrombus formation over a range of operation conditions using these pumps [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%